Pendekatan Muhasabah Diri dalam Konseling Individu untuk Mengubah Perilaku Playing Victim Anak - Risa Pitria; Kusnadi Kusnadi; Lena Marianti (Scidacplus, 2025)
This study examines the application of the Muhasabah Diri approach in individual counselling to change children's playing victim behaviour. The research is qualitative in nature, aiming to understand the subjective experience and behavioural transformation of children through the counselling process. The research subjects included three children in an elementary school in Palembang who showed a tendency of playing victim behaviour. Data were collected through in-depth interviews, observation, and documentation, then analysed using the Miles and Huberman qualitative data analysis model. The results showed that the Muhasabah Diri approach was effective in increasing children's self-awareness, responsibility, and emotion regulation, thereby reducing their tendency to play victim. The counselling process involves diagnosis, prognosis, therapy, and evaluation stages that are tailored to the developmental needs of children. This study concludes that Muhasabah Diri is a potential approach in individual counselling to shape a proactive and resilient mindset in children.